2018
DOI: 10.3390/ijms19103211
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electromagnetic Fields Increase Pigmentation through the p-ERK/p-p38 Pathway in Zebrafish (Danio rerio)

Abstract: Melanogenesis is a biological process resulting in the production of melanin pigment, which plays an important role in the prevention of sun-induced skin injury, and determines hair and skin color. So, a wide variety of approaches have been proposed to increase the synthesis of melanin. This study evaluated the effects of pulsed electromagnetic fields (PEMFs) on the pigmentation of zebrafish (Danio rerio) in vivo. We stimulated pigmentation in zebrafish by using specific frequencies and intensities of PEMFs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Furthermore, the expression of other melanogenic markers, such as tyrosinase-related protein 1 (TRP-1), tyrosinase-related protein 2 (TRP-2), and microphthalmia-associated transcription factor (MITF), are known to affect melanin synthesis in melanocytes [ 20 ]. Of note, in a recent study, it was found that pulsed electromagnetic fields (PEMFs) (60 Hz) induced skin pigmentation in zebrafish by increasing the activity of TRP-1, mediated by the phosphorylation of ERK and p38 [ 21 ], reflecting that melanin synthesis and melanocytes may be affected by EMFs [ 22 ]. However, it is not yet known whether 5G or even long-term evolution (LTE) EMFs could affect melanogenesis, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the expression of other melanogenic markers, such as tyrosinase-related protein 1 (TRP-1), tyrosinase-related protein 2 (TRP-2), and microphthalmia-associated transcription factor (MITF), are known to affect melanin synthesis in melanocytes [ 20 ]. Of note, in a recent study, it was found that pulsed electromagnetic fields (PEMFs) (60 Hz) induced skin pigmentation in zebrafish by increasing the activity of TRP-1, mediated by the phosphorylation of ERK and p38 [ 21 ], reflecting that melanin synthesis and melanocytes may be affected by EMFs [ 22 ]. However, it is not yet known whether 5G or even long-term evolution (LTE) EMFs could affect melanogenesis, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperpigmentation was characterized by the presence of melanocytes in control and anisodamine‐treated groups (1.3, 2.6, and 5.2 mM) according to the reported method (Y. M. Kim et al, 2018) at 48, 72, and 120 hpf. The results indicated that larvae exposed to high dose of anisodamine showed the hyperpigmentation in the head and dorsal regions at 72 and 120 hpf (Figure 3B,C).…”
Section: Resultsmentioning
confidence: 99%
“…Commonly, zebrafish is the gold standard for evaluate the harmful effects of many xenobiotics such as chemicals compounds or nanomaterials [26], but recently it has been considered a predictive model able to evaluate radio frequency effects. For example, Kim and colleagues (2018) have investigated the pro-pigmentation effect of pulsed electromagnetic fields (PEMFs) in zebrafish model [27]. Their results suggest that PEMFs, at an optimal intensity and frequency, promote pigmentation and then PEMFs are useful tool for treating gray hair with reduced melanin synthesis in the hair shaft, or hypopigmentation-related skin disorders.…”
Section: Discussionmentioning
confidence: 99%